2020
DOI: 10.3390/risks9010002
|View full text |Cite
|
Sign up to set email alerts
|

Are Investors’ Attention and Uncertainty Aversion the Risk Factors for Stock Markets? International Evidence from the COVID-19 Crisis

Abstract: In this paper, we examine the impact of investors’ attention to COVID-19 on stock market returns and the moderating effect of national culture on this relationship. Using daily data from 34 countries over the period 23 January to 12 June 2020, and measuring investors’ attention with the Google search volume (GSV) of the word “coronavirus” for each country, we find that investors’ enhanced attention to the COVID-19 pandemic results in negative stock market returns. Further, measuring the national culture with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…As to the COVID-19 disease specifically, results are in line with studies that have demonstrated the correlation between internet user attention (typically Google metrics)as a gauge of panic and fearand either market returns (Costola et al, 2020;Vasileiou, 2020;Iyke and Ho, 2021;Shear et al, 2021;Smales, 2021;Subramaniam and Chakraborty, 2021) or their volatility (Ly ocsa et al, 2020). The present study evaluates the impact of SM user attention on the local Australian financial market, here proxied by the topic-related number of Tweets and similarly to Valle-Cruz et al (2021)their negative content.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As to the COVID-19 disease specifically, results are in line with studies that have demonstrated the correlation between internet user attention (typically Google metrics)as a gauge of panic and fearand either market returns (Costola et al, 2020;Vasileiou, 2020;Iyke and Ho, 2021;Shear et al, 2021;Smales, 2021;Subramaniam and Chakraborty, 2021) or their volatility (Ly ocsa et al, 2020). The present study evaluates the impact of SM user attention on the local Australian financial market, here proxied by the topic-related number of Tweets and similarly to Valle-Cruz et al (2021)their negative content.…”
Section: Resultssupporting
confidence: 86%
“…These studies, none of them dedicated uniquely to the Australian market, typically use Google metrics (GSVs or GTs) with search terms such as "coronavirus" as a proxy of investor attention and fear (Costola et al, 2020;Vasileiou, 2020;Iyke and Ho, 2021;Ly ocsa et al, 2020;Shear et al, 2021;Smales, 2021;Subramaniam and Chakraborty, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCI world index have been widely used as the international equity market benchmark (e.g. ( Shear et al 2020 )). As Shown in Table 6 , our main results still hold after controlling for VIX and MSCI world index.…”
Section: Resultsmentioning
confidence: 99%
“…These contagion effects were found in both returns and stock market volatility. Shear et al (2021) in their study noted that increased investor attention to the COVID-19 pandemic resulted in negative stock market returns. This was particularly strong in countries where the investors held higher cultural values associated with avoiding uncertainty.…”
Section: Literature Reviewmentioning
confidence: 98%